Sosialisasi dan Pelatihan Pemanfaatan Sampah Organik Sebagai Eco-Enzyme Kepada Wanita Pesisir Pulau Santen, Banyuwangi - Wazirotus Sakinah; Hery Indria Dwi Puspita; Rudianto Rudianto; Saifurridzal Saifurridzal; Gandu Eko Julianto Suyoso (Journal of Community Development, 2022)
Banyuwangi has quite a lot of coastal areas. However, the negative impact of many coastal areas is that garbage is generally disposed of in the waters starting from the river which will eventually empty into the sea or directly dumped into the open sea. The mindset of Indonesian people including Banyuwangi residents who consider the sea as a garbage dump has not changed much. Santen island is one of the beaches in Banyuwangi with less waste management. As a solution to these problems, socialization is needed to increase awareness to the community and provide training to the community in handling organic waste. Socialization and training conducted is the utilization of organic waste as Eco-Enzyme with partners are coastal women. Eco-Enzyme is. This PkM implementation method consists of five stages, namely Pre-activity, presentation, Breefing training, training, and Evaluation and closing. Participants who attended this activity were 23 women of various ages. On the day of the training, the participants had prepared all the materials, then the organizing team divided the participants into 4 groups. For the ratio of ingredients for making this eco-enzyme is 1: 3: 10, where 1 is for sugar in grams, 3 is for fruit skin or vegetable scraps in grams, and 10 is water in mL. The socialization of the material on the first day increased participants' awareness of the importance of waste management and participants' enthusiasm in making eco-enzymes. Each participant in each group made eco-enzyme according to the instructions from the presenter.After three months, the participants were able to use Eco-Enzyme products as glass cleaners, toilet cleaners and bathrooms, while the pulp became fertilizer for ornamental plants in their homes.